Preface: 3rd International Conference on Management Engineering and Economic Analysis (MEEA 2024) - Pitman, Curitis; Liu, Xiupeng (Transactions on Economics, Business and Management Research, 2024)
The 2024 3rd International Conference on Management Engineering and Economic Analysis (MEEA 2024) was held in London, United Kingdom during August 17-18, 2024. This conference is to bring together innovative academics and experts in the fields of management engineering, business statistics, marketing strategies, financial economics and economic analysis to a common forum. The primary goal of the conference is to promote research and developmental activities and another goal is to promote information interchange between researchers, developers, engineers, students, and practitioners working all around the world.The conference model of MEEA 2024 was divided into two sessions, including oral presentations and keynote speeches. In the first part, some scholars, whose submissions were selected as the excellent papers, were given 10-15 minutes to perform their oral presentations one by one. Then in the second part, keynote speakers were each allocated 35-45 minutes to hold their speeches. We are glad to share with you that we received lots of submissions from the conference and we selected a bunch of high-quality papers and compiled them into the proceedings after rigorous reviewing.We are really grateful to the keynote speakers, session chairs, organizing committee members, student volunteers, and publication house. Also, we are thankful to all the authors for contributing a large number of papers in the conference. It was the quality of their presentations and their passion to communicate with the other participants that really make this conference series a great success.MEEA 2024 Organizing CommitteesLondon, United Kingdom